Coefficient of R‐R interval variations under deep breathing load in patients with wild‐type transthyretin amyloid cardiomyopathy: A case‐control study. Issue 1 (30th November 2022) - Nagayoshi, Yasuhiro; Kawano, Hiroaki; Nishihara, Taiki; Morikawa, Kei; Nagano, Haruka; Hanatani, Shinsuke; Sakaino, Naritsugu; Tsujita, Kenichi
Abstract: Background and Aims: An autonomic nervous disorder is an important characteristic of cardiac amyloidosis; however, the prevalence of autonomic dysfunction in wild‐type transthyretin amyloidosis (ATTRwt ) has not been established. Analysis of the R‐R interval coefficient of variation (CVR‐R) is a noninvasive method to measure parasympathetic activity. We aimed to assess autonomic dysfunction of ATTRwt and determine the utility of CVR‐R for the detection of ATTRwt in other cardiac diseases. Methods: This is a single‐center, retrospective, case‐control study. Fifty patients with heart failure (HF) were studied. The etiologies of HF were as follows: ATTRwt, n = 10; previous myocardial infarction (MI), n = 20; and left ventricular hypertrophy (LVH) due to other disease processes (e.g., aortic stenosis), n = 20. We measured the CVR‐R at rest (CVR‐Rrest ), CVR‐R with deep breaths (CVR‐Rbreath ), and the change rate (CVR‐Rdiff rate) . The relative change formula is as follows: CVR‐Rdiff rate = (CVR‐Rbreath − CVR‐Rrest )/CVR‐Rrest × $× $ 100 (%). Results: There was no difference in the CVR‐Rrest levels among the three groups. The CVR‐Rdiff rate levels in the ATTRwt group were significantly lower (ATTRwt : −8.77 [−43.8 to 10.9]; LVH: 67.4 [38.7 to 89.4]; MI: 83.7 [60.4 to 142.9]). Based on the receiver operative characteristic curve analysis to identify ATTRwt in HF, the best cut‐off value for the CVR‐Rdiff rate was 19.7 (area under the curve: 0.848). Conclusion: Our data suggested autonomic dysfunction in patients with ATTRwt . Measurement of the CVR‐R in HF patients may be a convenient support tool for the detection of ATTRwt .